Negative Politeness Strategies in Uglies Character Interactions - Ranti, Dewi; Mubarak, Zia Hisni (PROJECT (Professional Journal of English Education), 2025)
This study examines negative politeness strategies in character dialogue, aiming to reveal how linguistic choices minimize face-threatening acts (FTAs) to maintain social harmony. Using Brown and Levinsons politeness theory, the analysis draws from a qualitative descriptive design, with data sourced from the movie Uglies and collected through observational, non-participatory methods, recorded via note-taking. A pragmatic identity method and equalizing technique were applied to analyze 216 instances of negative politeness, identifying “Question, Hedge” as the most frequent strategy (41 instances), reflecting a strong preference for indirectness to soften statements and avoid imposing on the listener. This was followed by “Be Pessimistic” and “Apologize” with 25 instances each, indicating that expressions of doubt and regret were also commonly used to mitigate imposition. Other strategies included “Minimize the Imposition” and “Give Deference” (24 instances each), “Be Conventionally Indirect” (20), “Go on Record as Incurring a Debt, or as Not Indebting” (18), “Impersonalize” and “State the FTA as a General Rule” (14 each), and “Nominalize” (11). The findings suggest a consistent preference for indirectness and deference to protect negative face, supporting respectful interactions and reinforcing social balance among characters.